Html 5 Black Book : Covers Css 3, Javascript, Xml, Xhtml, Ajax, Php And Jquery - DT Editorial services (New Delhi, Dreamtech Press, 2022)
HTML5 Black Book is the one-time reference book, written from the Web professional?s point of view, containing hundreds of examples and covering nearly every aspect of HTML5. It will help you to master various Web technologies, other than HTML5, including CSS3, JavaScript, XML and AJAX. If you are a Web designer or developer, then this book is your introduction to new features and elements of HTML5, including audio and video media elements, the canvas element for drawing, and many others.
Keywords: HTML 5 I CSS3 I JavaScript I XML I XHTML I AJAX I PHP I jQuery I MCA